Effect of low-dose ionizing radiation on luminous marine bacteria: radiation hormesis and toxicity. (April 2015) - Kudryasheva, N.S.; Rozhko, T.V.
Abstract: The paper summarizes studies of effects of alpha- and beta-emitting radionuclides (americium-241, uranium-235+238, and tritium) on marine microorganisms under conditions of chronic low-dose irradiation in aqueous media. Luminous marine bacteria were chosen as an example of these microorganisms; bioluminescent intensity was used as a tested physiological parameter. Non-linear dose-effect dependence was demonstrated. Three successive stages in the bioluminescent response to americium-241 and tritium were found: 1 – absence of effects (stress recognition), 2 – activation (adaptive response), and 3 – inhibition (suppression of physiological function, i.e. radiation toxicity). The effects were attributed to radiation hormesis phenomenon. Biological role of reactive oxygen species, secondary products of the radioactive decay, is discussed. The study suggests an approach to evaluation of non-toxic and toxic stages under conditions of chronic radioactive exposure. Graphical abstract: Highlights: Luminous bacteria demonstrate nonlinear dose-effect relation in radioactive solutions. Response to low-dose radiation includes 3 stages: threshold, activation, inhibition. ROS are responsible for low-dose effects of alpha-emitting radionuclides. Luminous marine bacteria are a convenient tool to study radiation hormesis.